Improving Primary Students' Reading Engagement and Critical Literacy through Interactive Read-Aloud - Istihari, Istihari (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
This study explores reading activity using the Interactive Read-aloud approach to foster students' reading engagement and critical literacy. It also examines teachers' strategies to make interactions easier in an EFL classroom. In order to address the research problems, an exploratory sequential mix method was used, which included classroom observation, written papers, and an experiment in the classroom. The result of the study revealed that several strategies in applying critical literacy during interactive read-aloud were identified: juxtaposition, problem-solving, bookmark technique, say something, connection stem, switching and thinking hats. The test score of the experimental group has shown significant improvement from using the Interactive read-aloud approach, from 71.47 on the pretest to 87.47 on the posttest. The students also expressed varied enthusiasm and agreement regarding the benefits and enjoyment of Interactive Read-aloud. It is hoped that the practice of Interactive read-aloud can be widely used by teachers, parents, or educational practitioners to engage students in reading, enhance their motivation, and foster their critical literacy.